The prevalence of hypertension among young adults in a rural population of North India - Zafar, Khwaja Saifullah; Ram, Vidya Sagar; Kumar, Manoj; Gupta, Manish; Kumar, Sushil; Verma, Vivek Kumar; Singh, Prafulla Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Most of the studies on hypertension provided the data on older age group. Most of the times, younger population remains unaddressed as they are assumed to be at a lower risk of developing the disease. So, the study on prevalence of hypertension among younger age group and their socio-demographic variables provides the guide for requirements of any intervention. Objective of present study is to estimate the prevalence of Hypertension among young adults in a rural population of central India. Methods: We collected data on socio-demographic characteristics and hypertension status from 1061 subjects aged 18–40 years. Relevant clinical parameters were collected (blood pressure recordings and anthropometric measurements). Results: Hypertension was detected in 188 of the 1061 subjects (17.7%). Prevalence among men was higher (18.8% compared to 15.2% among women). A total of 40.2% of the subjects was found to have pre-hypertension. Higher prevalence of hypertension was seen among those with a history of smoking. Conclusions: Most of the young adults with raised blood pressure were previously undiagnosed. A large number of subjects had prehypertension. Their early identification facilitates early, active management of blood pressure and formulation of preventive strategies thereby decreasing morbidity and mortality due to cardiovascular diseases and hypertension.